Modelling knowledge sharing behaviour using self-efficacy as a mediator - Brooke, Jenefer; Mohd Rasdi, Roziah; Abu Samah, Bahaman (Emerald Publishing, 2017)
Purpose: The purpose of this paper is to examine the direct and indirect relationships between individual-related factors and environmental-related factors with the knowledge sharing behaviour through the mediating role of self-efficacy among successful farmers in selected states in Malaysia. Design/methodology/approach: The research used survey method and included 241 participants from Johor, Negeri Sembilan and Selangor. The analysis was conducted using the partial least square structural equation modelling to achieve the research objectives. Findings: The findings indicate that individual-related factors (e.g. enjoyment in helping others, training and prior experience) and environmental-related factors (e.g. social support and trust) have significant influence on the knowledge sharing behaviour. The results also reveal that self-efficacy mediates the relationships between prior experiences (individual-related factor), social support, trust (environmental- related factor) and the knowledge sharing behaviour. Practical implications: Agriculture officers should emphasize on farmers’ personal and social factors to encourage the knowledge sharing behaviour among the agriculture communities of successful farmers. Originality/value: The research yields a theoretical framework that outlines the potential of six key factors in explaining the knowledge sharing behaviour among successful farmers. The factors can be considered in developing structured knowledge-sharing programs.